Association of pheochromocytoma and primary hyperaldosteronism in a 50-year-old man. Issue 1 (March 2015) - Hugo, Marie; Cremer, Antoine; Tauzin-Fin, Patrick; Ballanger, Philippe; Gosse, Philippe
Abstract : The association of primary hyperaldosteronism and pheochromocytoma is very rare, but poses diagnostic and therapeutic problems exemplified in the following case. A 50-year-old man was referred for resistant and severe hypertension. Laboratory tests showed low serum potassium, primary hyperaldosteronism, and an increase in urinary norepinephrine and metanephrine. An adrenal scan indicated a nodule of the right gland of 35×30 mm with a spontaneous density of 12 HU. The initial diagnosis was that of a Conn's adenoma. A right adrenalectomy was performed. The tissue removed was a pheochromocytoma. The postoperative course was marked by persistence of high blood pressure. On laboratory tests, levels of urinary metanephrines were normalized, but primary hyperaldosteronism was still present. Thus, the case was finally diagnosed as a bilateral adrenal hyperplasia and unilateral pheochromocytoma. Five cases of involvement of both the adrenal cortex and the medulla have been reported. The scarcity of the cases published favors a fortuitous association. However, other possibilities could be envisaged. A close relation between the cortical and medullary cells has been shown that may play an important role in the regulation of the endocrinal function. Another possibility could be stimulation by adrenaline of the release of adrenocorticotropic hormone and renin, inducing cortical hyperplasia and stimulating the secretion of aldosterone, which could become self-perpetuating. Finally, there may be a genetic predisposition to the endocrine dysplasias involving a double hormonal secretion by the adrenal gland. In conclusion, the association of pheochromocytoma and primary hyperaldosteronism can present in the same patient and needs to be considered on the basis of the clinical and biochemical findings.